The onset and severity of acute opioid toxicity in heroin overdose cases: a retrospective cohort study at a supervised injecting facility in Melbourne, Australia. (2nd November 2022) - Stam, Nathan C.; Cogger, Shelley; Schumann, Jennifer L.; Weeks, Anthony; Roxburgh, Amanda; Dietze, Paul M.; Clark, Nicolas
Abstract: Aim: To differentiate the severity of acute opioid toxicity and describe both the clinical and physiological features associated with heroin overdose in a cohort of witnessed overdose cases. Methods: Witnessed heroin overdose cases over a 12-month period (30 June 2018 – 30 June 2019) at the Medically Supervised Injecting Room (MSIR) in Melbourne, Australia were examined. The severity of acute opioid toxicity was classified according to the level of clinical intervention required to manage the overdose cases where an escalating level of care was provided. Heroin overdose cases were classified into one of three graded severity categories and a fourth complicated heroin overdose category. Results: A total of 1218 heroin overdose cases were identified from 60, 693 supervised injecting visits over the study period. On the spectrum of toxicity, 78% ( n  = 955) of overdose cases were classified as Grade 1 severity, 7% ( n  = 83) as Grade 2 severity, and 13% ( n  = 161) as Grade 3 acute opioid toxicity severity cases, as well as 2% ( n  = 19) classified as complicated heroin overdose cases. The median onset time for heroin overdose cases was 17 min (IQR 11–28 min) from the time the individual was ready to prepare and inject heroin until clinical intervention was initiated. Conclusion: We demonstrated that heroin overdose is a dynamic illness and cases differ in the severity of acute opioid toxicity. The risk of airway occlusion including positional asphyxia was an early and consistent feature across all levels of toxicity, while exaggerated respiratory depression together with exaggerated depression of consciousness was increasingly observed with greater levels of toxicity. We also demonstrated the importance of early intervention in overdose cases, where in a large cohort of heroin overdose cases there were no fatal outcomes, a very low hospitalisation rate and most cases were able to be managed to clinical resolution on-site.